2017
DOI: 10.1142/s0218810417500393
|View full text |Cite
|
Sign up to set email alerts
|

Non-tuberculous Mycobacterium or Fungus Induced Chronic Tenosynovitis with Rice Body of the Hand

Abstract: Background: Chronic tenosynovitis of the wrist and hand is commonly seen by orthopedists, especially hand surgeons. However, cases with rice body formation are comparatively rare. Thus, we retrospectively reviewed the cases of chronic tenosynovitis in our department and evaluated the necessity of antibiotic therapy in the early post-surgical stage. Methods: We analyzed the medical and surgical records of patients who had undergone surgery for chronic tenosynovitis with rice body formation in our department fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 18 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Rice bodies caused in tenosynovitis are reported in rheumatoid arthritis, tuberculosis, and NTM infection ( 1 ). The pathogenesis of rice body formation remains unclear, but experts have suggested that they arise from microinfarcted synovium or that the early rice body appears de novo and causes progressive enlargement by fibrin deposition ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice bodies caused in tenosynovitis are reported in rheumatoid arthritis, tuberculosis, and NTM infection ( 1 ). The pathogenesis of rice body formation remains unclear, but experts have suggested that they arise from microinfarcted synovium or that the early rice body appears de novo and causes progressive enlargement by fibrin deposition ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infectious arthritis in SLE often resembles a disease flare and hence is difficult to diagnose. Rice-body formations, which could be detected by imaging modalities such as magnetic resonance imaging (MRI), have been reported in non-tuberculosis mycobacterium (NTM) tenosynovitis ( 1 , 2 ). We herein report a case of refractory arthritis in an SLE patient, who was diagnosed with NTM tenosynovitis after the detection of rice bodies on MRI and the confirmation of Mycobacterium chelonae on a lower temperature tissue culture.…”
Section: Introductionmentioning
confidence: 99%
“…Pyogenic tenosynovitis was observed to have worse outcomes when the organism was Staphylococcus and when antimicrobial therapy was delayed 119 . Kanavel signs were observed to be sensitive but not specific 120 , and in 1 center's experience, when rice bodies were found in chronic tenosynovitis, the causative organism was often NTM, fungus, or unidentified 113 .…”
Section: Hand Surgerymentioning
confidence: 92%
“…Pyogenic tenosynovitis was observed to have worse outcomes when the organism was Staphylococcus and when antimicrobial therapy was delayed 119 . Kanavel signs were observed to be sensitive but not specific 120 , and in 1 center's experience, when rice bodies were found in chronic tenosynovitis, the causative organism was often NTM, fungus, or unidentified 113 .…”
Section: Hand Surgerymentioning
confidence: 95%
“…Atypical infections caused by Mycobacterium tuberculosis (TB) [103][104][105][106][107] , nontuberculous mycobacteria (NTM) 104,[108][109][110][111][112][113] , and fungi 104,[114][115][116][117] were associated with delays in diagnosis, and the authors suggest a need for a heightened index of suspicion 103,104,110 , and when ordered, 2.4% of cultures were positive for acid-fast bacilli (AFB) and 5.3% were positive for fungi 104 . M. marinum is the most common NTM, but several other species were also investigated [108][109][110]112,113 . Clinical findings were described, and about half of the cases occurred in healthy hosts who had no apparent portal of entry or causative event 103,107,111 .…”
Section: Hand Surgerymentioning
confidence: 99%